Pengaruh Keaktifan Organisasi Terhadap Prestasi Akademik Mahasiswa Fakultas Kedokteran - Afridatul Luailiyah; Akbar Zadal Hilmi; Menik Sahariani (Fakultas Kedokteran, Universitas Sebelas Maret, 2022)
Background: The activeness of students in organizations is considered as one of the things that influences the learning achievement of students. Participating in organizations can also make students have experience and practice management. Medical students are required to master seven areas of competence including noble professionalism, insight and personal development, effective communication, information management, scientific foundation of medical science, clinical skills and management of health problems. These competencies can be achieved through academic learning or intra and extracurricular activities. The purpose of this study was to determine the effect of the level of organizational activeness with a cumulative achievement index (CAI) for students of the medical faculty of Unissula Semarang. Methods: Analytic observational research with pre-posttest design. A total of 111 students of the medical faculty of Unissula Semarang class of 2016 were the subject of this study. Organizational activity was assessed by a questionnaire containing 12 questions about the quantity of organization. The CAI value of semester 2 and 6 and its difference were used. The effect of organizational activity on CAI was analyzed by the Wilcoxon and Kruskal Wallis tests. Results: The GPA value for semester 6 was significantly higher than in semester 2 for all of the organizational activities level includes low, medium and high categories (p <0.05). However, the increase in the value of the CAI was not related to the organizational activity level (p> 0.05). Conclusion: The level of activeness in organizing has no effect on the CAI of students of the medical faculty of Unissula Semarang.